Insurantial imaginaries: Some implications for home-owning democracies. Issue 136 (November 2022) - Booth, Kate; Davison, Aidan; Hulse, Kath
Abstract: 'Insurantial imaginaries' describes the shared structures of comprehension and action that establishes the social value of insurance and its practical influence. As insurance is a bricolage of economic, legal, political, cultural and moral elements that vary across time and space, for insurance to be intelligible and functional, these imaginaries render this dynamic complexity into stable and discrete forms. In this paper, we explore one such imaginary constituted through the intersection of housing and insurance norms, vis a vis house and contents insurance, in home-owning democracies. Drawing on the cases of Australia and the United Kingdom, we observe how a rise in renting in these countries is resulting in an increase in underinsurance, with renters less likely to insure their assets. This is refashioning a long-standing insurantial imaginary shaped by socio-cultural aspirations for home-ownership, liberal norms of individual autonomy, and links between home-ownership and democracy, including participation in voting. In observing that this imaginary valorises home-ownership and insurance, and problematises renting and underinsurance, we draw attention to the covert power of insurance in co-constituting everyday practices and identify a novel spatialised insurantial imaginary. In grounding our analysis within home-owning democracies, we also make a broader contribution to economic and financial geography by extending understanding of the complex spatial nature of financial mechanisms and processes, and how market-based economies appear to be reconfiguring democracy.